2014
DOI: 10.1056/nejmoa1303359
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Vancomycin Resistance in a Community-Associated MRSA Lineage

Abstract: SUMMARY We report the case of a patient from Brazil with a bloodstream infection caused by a strain of methicillin-resistant Staphylococcus aureus (MRSA) that was susceptible to vancomycin (designated BR-VSSA) but that acquired the vanA gene cluster during antibiotic therapy and became resistant to vancomycin (designated BR-VRSA). Both strains belong to the sequence type (ST) 8 community-associated genetic lineage that carries the staphylococcal chromosomal cassette mec (SCCmec) type IVa and the S. aureus prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
99
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 25 publications
(43 reference statements)
4
99
0
5
Order By: Relevance
“…The emergence of multidrug-resistant MRSA isolates acquiring glycopeptide resistance during vancomycin therapy documents the urgent need for controlling the use of antibiotics (42). Recent research efforts have been directed at developing antiinfective therapies against S. aureus, focusing on small molecules that interfere with virulence gene regulation (43).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of multidrug-resistant MRSA isolates acquiring glycopeptide resistance during vancomycin therapy documents the urgent need for controlling the use of antibiotics (42). Recent research efforts have been directed at developing antiinfective therapies against S. aureus, focusing on small molecules that interfere with virulence gene regulation (43).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, intermediate resistance to vancomycin in patients has been described, but few studies have reported colonization of health professionals by these strains 32 . The fi rst case of transferable vancomycin resistance in a communityassociated MRSA strain was reported in a Brazilian hospital, indicating that the presence of MRSA containing the vanA gene could be a future public problem 33 . Some studies that use ribotyping-PCR to assess genetic similarity also present ample polymorphisms, as in our study, considering the number of ribotypes observed, thus indicating dispersion in the hospital sectors 34,35 , but these studies do not make comparisons of dispersion between classes of patients and professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, vancomycin was considered as the drug of choice for treatment of MRSA infections until recently (2,4). In the past decade, vancomycin-resistant strains of S. aureus have been reported from different parts of the world (5,6). This fact has raised concerns about the efficacy of vancomycin for treatment of infections caused by S. aureus in near future (7,8).…”
Section: Introductionmentioning
confidence: 99%